El derecho de acceso al procedimiento administrativo en trámite: el dilema entre interesados y terceros - EDUARD-VALENTIN PAVEL (Revista Vasca de Administración Pública)
This study aims to analyze certain vicissitudes of the right of access to public information of interested parties and third parties in pending administrative proceedings underway in the light of the first additional provision of Act 19/2013, of December 9, 2013, on transparency, access to public information and good governance. On the one hand, the legal regime applicable to the right of access of interested parties in administrative proceedings is evaluated, especially, whether they are allowed to resort to the technique of regulatory gleaning to take advantage from those aspects of the transparency legislation that are more favorable to them. And, on the other hand, it is analyzed whether the right of access to the procedures in progress is reserved to the interested parties or, on the contrary, whether non-interested third parties can also have access, taking into consideration the supplementary nature of the transparency legislation with respect to the special regimes of access to information. This last aspect becomes the central idea of the work, insofar as it is argued that the law of administrative procedure only guarantees the right of access to ongoing procedures for interested parties, not for citizens in general.